Method for producing surface treatment film

The method addresses the limitations of existing technologies by using surface radical polymerization with a quaternary ammonium salt in a polymerization solution to form a surface treatment film with sufficient thickness, suitable for mass production and diverse applications.

JP7656298B2Active Publication Date: 2025-04-03DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021156933
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-27
Publication Date
2025-04-03
Estimated Expiration
2041-09-27

AI Technical Summary

Technical Problem

Existing methods for increasing the thickness of polymer layers formed with thick polymer brushes are limited by the need for high-pressure equipment and the use of specialized and costly ionic liquids, making them unsuitable for mass production.

Method used

A method for manufacturing a surface treatment film using surface radical polymerization of methacrylate-based monomers in the presence of a substrate with a functional group and a polymerization solution containing a quaternary ammonium salt as a solid organic salt, which allows for the formation of a polymer with high molecular weight and sufficient thickness without the need for high-pressure equipment or expensive ionic liquids.

Benefits of technology

This method enables the easy formation of a surface treatment film with sufficient thickness on a substrate using a highly versatile and cost-effective device or raw material, making it suitable for mass production and various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656298000001
    Figure 0007656298000001
  • Figure 0007656298000002
    Figure 0007656298000002
  • Figure 0007656298000003
    Figure 0007656298000003
Patent Text Reader

Abstract

To provide a method for producing a surface-treated film that can readily form a surface-treated film having sufficient thickness, on the surface of a substrate, using easily available versatile devices and raw materials.SOLUTION: A method for producing a surface-treated film includes the step in which, in the presence of a substrate having a functional group represented by the general formula (1) on its surface and a polymerization solution, a methacrylate monomer is subjected to surface radical polymerization to form a surface-treated film comprising a polymer (i), where the surface-treated film has a thickness of 400-3,000 nm, the polymerization solution is a solution in which an organic salt being solid at 25°C is dissolved in organic solvent, and the organic salt is a quaternary ammonium salt with its counterion being a halogen-free anion. (A is O or NH, R1 is a hydrogen atom, an alkyl group, an acyl group, or an aryl group, R 2 is an alkyl group or an aryl group, X is a chlorine atom or the like, * is a position of bonding to the substrate surface).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a surface treatment film. [Background technology]

[0002] As a method for modifying a substrate, a method is known in which a polymer having a group at its end capable of adsorbing or reacting with the substrate is applied to the substrate to form a physically or chemically bonded polymer layer on the substrate surface. Also known is a method in which a polymerizable group provided on the substrate surface is used as a starting point to polymerize a monomer to form a grafted polymer layer from the substrate surface.

[0003] In recent years, so-called "concentrated polymer brushes" have been studied, which are densely grafted onto a substrate using the technology of living radical polymerization developed in the 1990s. In these concentrated polymer brushes, polymer chains are grafted onto the substrate at high density with intervals of 1 to 4 nm. Such concentrated polymer brushes can modify the surface of a substrate, imparting characteristics such as low friction, suppression of protein adsorption, size exclusion properties, hydrophilicity, and water repellency (Patent Document 1).

[0004] However, it has been difficult to increase the thickness of conventional polymer layers formed with concentrated polymer brushes. Therefore, various methods have been proposed to increase the thickness of polymer layers formed with concentrated polymer brushes. For example, a method has been proposed in which living radical polymerization is performed under high pressure conditions to reduce the termination reaction rate and increase the polymer growth rate (Patent Document 2). In addition, a method has been proposed in which polymerization is performed in the presence of an ionic liquid to improve the polymer growth rate and form a polymer layer with an increased thickness (Patent Document 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-263819 [Patent Document 2] International Publication No. 2017 / 171071 [Patent Document 3] JP 2014-169787 A Summary of the Invention [Problem to be solved by the invention]

[0006] In the method proposed in Patent Document 2, it is necessary to apply a pressure of 100 to 400 MPa to the polymerization reaction system. Therefore, a pressure vessel capable of withstanding such high pressure is required, and a special device for applying pressure is also required, so that the method is not versatile and difficult to apply to mass production. In addition, in the method proposed in Patent Document 3, it is necessary to use an ionic liquid, which cannot be said to be versatile. In addition, strict dehydration and purification are required to obtain the ionic liquid, so that the method is difficult to apply to mass production.

[0007] The present invention has been made in consideration of the problems associated with the conventional techniques, and an object of the present invention is to provide a method for producing a surface treatment film that can easily form a surface treatment film having a sufficient thickness on the surface of a substrate using versatile and easily available equipment and raw materials. [Means for solving the problem]

[0008] That is, according to the present invention, there is provided a method for producing a surface treatment film as described below. [1] A process for forming a surface treatment film containing a polymer (i) having one end bonded to the surface of the substrate by surface radical polymerization of a methacrylate monomer in the presence of a substrate having on its surface a functional group represented by the following general formula (1) and a polymerization solution, wherein the number average molecular weight of the polymer (i) is 500,000 to 5,000,000 and the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.1 to 2.0, the thickness of the surface treatment film is 400 to 3,000 nm, and the amount of the polymer (i) bonded to the surface of the substrate is 1 nm or less of the surface of the substrate. 2the polymerization solution is a solution in which a solid organic salt is dissolved in an organic solvent at 25°C, the concentration of the organic salt being 10 to 90 mass%, and the organic salt is a quaternary ammonium salt whose counter ion is a non-halogen anion.

[0009] TIFF0007656298000001.tif31170 (In the general formula (1), A represents O or NH, R1 represents a hydrogen atom, an alkyl group, an acyl group, or an aryl group, R2 represents an alkyl group or an aryl group, X represents a chlorine atom, a bromine atom, or an iodine atom, and "*" represents the bonding position with the surface of the substrate.)

[0010] [2] The method for producing a surface treatment film according to the above [1], wherein the organic salt is represented by the following general formula (2) or (3):

[0011] TIFF0007656298000002.tif26170 (In the general formula (2), R3, R4, R5, and R6 each independently represent an alkyl group or a benzyl group having 1 to 18 carbon atoms, and A represents a non-halogen anion.)

[0012] TIFF0007656298000003.tif37170 (In the general formula (3), R7 represents a hydrogen atom or an alkyl group having 1 to 18 carbon atoms, R8 represents an alkyl group having 1 to 18 carbon atoms, and A represents a non-halogen anion.)

[0013] [3] The method for producing a surface treatment film according to [1] or [2], wherein the non-halogen anion is at least one selected from the group consisting of a methanesulfonate ion, an ethanesulfonate ion, a benzenesulfonate ion, and a toluenesulfonate ion. [4] The method for producing a surface treatment film according to any one of [1] to [3] above, wherein the organic solvent is at least one selected from the group consisting of alkylene (carbon number 2 to 4) glycols, poly(n=2 to 3) alkylene (carbon number 2 to 4) glycols, alkylene (carbon number 2 to 4) glycol monoalkyl (carbon number 1 to 4) ethers, and poly(n=2 to 3) alkylene (carbon number 2 to 4) glycol monoalkyl (carbon number 1 to 4) ethers. [5] The method for producing a surface treatment film according to any one of [1] to [4], wherein the functional group represented by the general formula (1) is at least one of a 2-bromo-2-methylpropanoyloxy group and a 2-bromo-2-methylpropanoylamino group. [6] The method for producing a surface-treated film according to any one of [1] to [5] above, comprising surface-initiating living radical polymerization of the methacrylate monomer under a pressure condition of 10 to 200 MPa. Effect of the Invention

[0014] According to the present invention, a method for producing a surface treatment film can be provided that enables a surface treatment film having a sufficient thickness to be easily formed on the surface of a substrate using versatile and easily available equipment and raw materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] <Method of manufacturing surface treatment film> Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the following embodiments. The method for producing a surface treatment film of the present invention comprises a step of performing surface radical polymerization of a methacrylate monomer in the presence of a substrate having a functional group represented by the following general formula (1) on its surface and a polymerization solution, to form a surface treatment film containing a polymer (i) having one end bonded to the surface of the substrate. The number average molecular weight of the polymer (i) is 500,000 to 5,000,000, and the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.1 to 2.0. The thickness of the surface treatment film formed is 400 to 3,000 nm, and the amount of the polymer (i) bonded to the surface of the substrate is 1 nm per 1 nm of the substrate surface. 2The number of molecular chains per unit area is 0.1 or more. The polymerization solution is a solution in which a solid organic salt is dissolved in an organic solvent at 25° C., and the concentration of the organic salt is 10 to 90 mass %, and the organic salt is a quaternary ammonium salt whose counter ion is a non-halogen anion. The method for producing the surface treatment film of the present invention (hereinafter, also simply referred to as the "production method (of the present invention)") will be described in detail below.

[0016] TIFF0007656298000004.tif31170 (In the general formula (1), A represents O or NH, R1 represents a hydrogen atom, an alkyl group, an acyl group, or an aryl group, R2 represents an alkyl group or an aryl group, X represents a chlorine atom, a bromine atom, or an iodine atom, and "*" represents the bonding position with the surface of the substrate.)

[0017] The substrate has a functional group represented by general formula (1) on its surface. The substrate can be obtained by introducing a functional group represented by general formula (1) that functions as a polymerization initiation group onto the surface of a substrate (substrate body) of a conventionally known material and shape. The substrate body may be any of natural products, artificial products, inorganic materials, and organic materials. Examples of the shape of the substrate body include lumps, fine particles, powders, sheets, films, pellets, and plates. Specific examples include mechanical parts such as metals, metal oxides, metal nitrides, metal carbides, ceramics, wood, silicon compounds, thermoplastic resins, thermosetting resins, cellulose, and glass, as well as films, fibers, and sheets. More specific examples of the substrate body include silicon substrates; glass substrates; metal plates such as stainless steel; ceramic plates formed of ceramics such as alumina, silicon carbide, and boron nitride; ITO films; plate-shaped or film-shaped substrates such as plastic plates and plastic films; fibrous substrates such as glass fibers and carbon fibers; and the like. The substrate may also be a filler-shaped material such as pigments, silica, and magnetic powder.

[0018] Examples of the functional group (polymerization initiating group) represented by general formula (1) include a 2-chloropropanoyloxy group, a 2-bromopropanoyloxy group, a 3-iodopropanoyloxy group, a 2-chloropropanoylamino group, a 2-bromopropanoylamino group, a 2-iodopropanoylamino group, a 2-chloro-2-methylpropanoyloxy group, a 2-bromo-2-methylpropanoyloxy group, a 2-iodo-2-methylpropanoyloxy group, a 2-chloro-2-methylpropanoyloxy group, a 2-iodo-2-methylpropanoyloxy group, a 2-chloro-2-methylpropanoyloxy group, a 2-bromo-2-methylpropanoyloxy group, a 2-iodo-2-methylpropanoyloxy group, a 2-chloro ... arylamino group, 2-bromo-2-methylpropanoylamino group, 2-iodo-2-methyl-propanoylamino group, 2-chlorobutanoyloxy group, 2-bromobutanoyloxy group, 3-iodobutanoyloxy group, 2-chlorobutanolamino group, 2-bromobutanoylamino group, 2-iodobutanoylamino group, chlorophenylacetyloyloxy group, bromophenylacetyloyloxy group, iodophenylacetyloyloxy group, chlorophenylacetyl iodomethylphenylacetyloylamino group, bromophenylacetyloylamino group, iodomethylphenylacetyloylamino group, chloromethylphenylacetyloyloxy group, bromomethylphenylacetyloyloxy group, iodomethylphenylacetyloyloxy group, chloromethylphenylacetyloylamino group, bromomethylphenylacetyloylamino group, iodomethylphenylacetyloylamino group, chlorodiphenylacetyloyloxy group, bromodiphenylacetyloyloxy group Examples of the aryl group include a 2-chloropropanoyloxy group, a 2-chloropropanoylamino group, a 2-bromo-2-methylpropanoyloxy group, and a 2-bromo-2-methylpropanoylamino group, and particularly preferably at least one of a 2-bromo-2-methylpropanoyloxy group and a 2-bromo-2-methylpropanoylamino group.

[0019] The polymerization initiator group can be introduced onto the surface of the substrate by dehydration condensation reaction of a compound having a polymerization initiator group and a silane coupling group such as a trimethoxysilyl group or a triethylsilyl group with a hydroxyl group on the substrate surface, or by dehydration condensation reaction of a silanol group previously applied to the substrate surface using a silane monomer such as tetraethoxysilane. In addition, a carboxylic acid halide or a carboxylic acid anhydride having a polymerization initiator group may be reacted with an organic hydroxyl group or an amino group on the substrate surface. Furthermore, the substrate may be coated with a polymer having a polymerization initiator group.

[0020] Methacrylate monomers have quaternary radicals at their polymerization terminals, making them less susceptible to termination reactions and facilitating the elimination of protective groups in living radical polymerization. This makes it possible to form a polymer (i) with a high molecular weight and to form a surface treatment film with a sufficient thickness.

[0021] Examples of the methacrylate monomer include aliphatic alkyl, alicyclic alkyl, aromatic, and ether group-containing methacrylates such as methyl, ethyl, propyl, butyl, isobutyl, t-butyl, hexyl, octyl, 2-ethylhexyl, decyl, isodecyl, dodecyl, stearyl, behenyl, cyclohexyl, t-butylcyclohexyl, trimethylcyclohexyl, tricyclodecyl, isobornyl, adamantyl, phenyl, benzyl, tetrahydrofurfuryl, and polyethylene glycol monomethyl ether; amino group-containing methacrylates such as dimethylaminoethyl and diethylaminoethyl; fluorinated alkyl group-containing methacrylates such as trifluoromethyl and perfluorooctyl; and dimethylsiloxane chain-containing methacrylates.

[0022] The polymerization solution is a solution in which a solid organic salt is dissolved in an organic solvent at 25°C. This organic salt is a quaternary ammonium salt with a non-halogen anion as a counter ion. Since the polymerization solution in which the organic salt is dissolved has high polarity, it is possible to accelerate the growth reaction of the polymer (i) by using this polymerization solution, and a surface treatment film with a larger film thickness can be formed. In addition, this polymerization solution is also preferable in that it can be easily prepared using an organic salt that is easily available and inexpensive, unlike ionic liquids, which are difficult to produce and relatively expensive.

[0023] Examples of organic solvents that can be used include alcohol-based solvents such as methanol, ethanol, and propanol; hydrocarbon-based solvents such as dodecane, toluene, and xylene; ketone-based solvents such as methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as ethyl acetate and butyl acetate; ether-based solvents such as tetrahydrofuran, dioxane, and ethylene glycol dimethyl ether; glycol-based solvents such as ethylene glycol, propylene glycol, and propylene glycol monomethyl ether; ester glycol-based solvents such as propylene glycol monomethyl ether acetate and diethylene glycol monomethyl acetate; amide-based solvents such as N-methylpyrrolidone, dimethylformamide, dimethylacetamide, and 3-methoxy-N,N-dimethylpropionamide; sulfur-based solvents such as dimethylsulfoxide; and urea-based solvents such as 1,3-dimethylimidazolidinone and tetramethylurea. Among these, alcohol-based solvents, glycol-based solvents, amide-based solvents, sulfur-based solvents, and urea-based solvents are preferred.

[0024] As the organic solvent, glycol-based solvents are more preferable, and at least one selected from the group consisting of alkylene (carbon number 2-4) glycol, poly(n=2-3) alkylene (carbon number 2-4) glycol, alkylene (carbon number 2-4) glycol monoalkyl (carbon number 1-4) ether, and poly(n=2-3) alkylene (carbon number 2-4) glycol monoalkyl (carbon number 1-4) ether is particularly preferable. More specifically, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-butanediol, 1,4-butanediol, ethylene glycol monomethyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, etc. can be mentioned. These organic solvents can easily dissolve the above-mentioned organic salt at a high concentration and are poor solvents for the polymer (i) formed. Therefore, by using a polymerization solution in which an organic salt is dissolved in these organic solvents, it is possible to form a polymer (i) having a higher molecular weight and to form a thicker surface treatment film. The most preferred organic solvents are ethylene glycol and propylene glycol.

[0025] The organic salt is a quaternary ammonium salt whose counterion is a non-halogen anion, and is a solid salt at 25°C. By performing surface radical polymerization using a polymerization solution containing this organic salt, it is possible to form a polymer (i) having a high molecular weight and to form a surface treatment film having a sufficient thickness. In addition, this organic salt is commercially available as a surfactant or phase transfer catalyst, and is inexpensive and easily available.

[0026] Examples of quaternary ammonium salts include tetraalkylammonium salts, trialkylbenzylammonium salts, trialkylarylammonium salts, trialkylhydroxyalkylammonium salts, trialkylacetylalkylammonium salts, trialkylbenzoylalkylammonium salts, 1-alkyl-3-alkylimidazolium salts, and alkylpyridinium salts.

[0027] The counter ion of the quaternary ammonium salt is a non-halogen anion. During surface radical polymerization, the halogen atom of the polymerization initiator group is released as a halogen radical to generate a carbon radical, and the generated carbon radical reacts with the monomer, and the released halogen radical is bonded to the monomer, thereby growing the molecular chain of the polymer. Here, if a halogen anion is present, a side reaction occurs due to interaction with the halogen radical, and the polymerization does not proceed or tends to stop midway, making it difficult to form a polymer with a high molecular weight. In contrast, by using a quaternary ammonium salt with a non-halogen anion as the counter ion, it is possible to form a polymer (i) with a high molecular weight and to form a surface treatment film with a sufficient thickness.

[0028] Examples of non-halogen anions include methanesulfonate ion, ethanesulfonate ion, benzenesulfonate ion, p-toluenesulfonate ion, methyl sulfate ester ion, ethyl sulfate ester ion, trifluoromethanesulfonate ion, tetrafluoroboron ion, pentafluoroline ion, bis(fluorosulfonyl)imide ion, and bis(trifluoromethanesulfonyl)imide ion. Among these, at least one selected from the group consisting of methanesulfonate ion, ethanesulfonate ion, benzenesulfonate ion, and toluenesulfonate ion, which are easy to synthesize, readily available, and inexpensive, is preferred. In addition, organic salts of zwitterions having an anion and a cation in the molecule can also be used. Specifically, organic salts having zwitterion groups such as carboxybetaine, sulfobetaine, and phosphorylcholine can be mentioned.

[0029] From the viewpoints of versatility, availability, low cost, and the like, it is preferable to use an organic salt represented by the following general formula (2) or (3).

[0030] TIFF0007656298000005.tif26170 (In the general formula (2), R3, R4, R5, and R6 each independently represent an alkyl group or a benzyl group having 1 to 18 carbon atoms, and A represents a non-halogen anion.)

[0031] TIFF0007656298000006.tif37170 (In the general formula (3), R7 represents a hydrogen atom or an alkyl group having 1 to 18 carbon atoms, R8 represents an alkyl group having 1 to 18 carbon atoms, and A represents a non-halogen anion.)

[0032] Examples of the quaternary ammonium salt constituting the organic salt represented by general formula (2) include tetramethylammonium salt, ethyltetramethylammonium salt, hydroxyethyltrimethylammonium salt, tetrapropylammonium salt, tetraethylammonium salt, tetrabutylammonium salt, tributylmethylammonium salt, dodecyltrimethylammonium salt, octyltrimethylammonium salt, benzyltrimethylammonium salt, benzyltriethylammonium salt, benzyltributylammonium salt, and benzyldodecyldimethylammonium salt.

[0033] Examples of the quaternary ammonium salt (pyridinium salt) constituting the organic salt represented by the general formula (3) include methylpyridinium salt, ethylpyridinium salt, cetylpyridinium salt, and methyl 4-methylpyridinium salt.

[0034] The organic salt is solid at 25°C. Organic salts that are liquid at 25°C are usually called ionic liquids, and are expensive and require complicated purification. In contrast, organic salts that are solid at 25°C are commercially available at low cost for use as surfactants, phase transfer catalysts, alkylating agents, and the like. However, since they cannot be used as polymerization solvents as they are, they are dissolved in an organic solvent to form a polymerization solution with increased polarity, which allows the formation of a polymer (i) having a high molecular weight and a surface treatment film of sufficient thickness. Furthermore, by using a polymerization solution in which this organic salt is dissolved, it is possible to proceed with the polymerization reaction even under high pressure conditions, and a surface treatment film of sufficient thickness can be formed using commercially available equipment. In addition, it is also possible to handle mass production and surface treatment of substrates of various shapes.

[0035] The concentration of the organic salt in the polymerization solution is 10 to 90% by mass, preferably 20 to 80% by mass, and more preferably 30 to 70% by mass. If the concentration of the organic salt is less than 10% by mass, a surface treatment film with a sufficient thickness cannot be formed. On the other hand, if the concentration of the organic salt is more than 90% by mass, the organic salt may remain insoluble in the organic solvent.

[0036] In the presence of a substrate and a polymerization solution, a methacrylate monomer is subjected to surface radical polymerization, preferably surface-initiated living radical polymerization, to form a surface treatment film that includes a polymer (i) whose one end is bonded to the surface of the substrate, preferably substantially composed of the polymer (i). Among surface-initiated living radical polymerizations, atom transfer radical polymerization (ATRP) is preferred, which is easy to introduce an initiator group. In the ATRP method, an organic halide is used as an initiator group, and a complex of a metal ion such as a copper ion or a ruthenium ion with a polyamine as a ligand is used as a catalyst. This catalyst abstracts a halogen atom from the initiator group as a radical, changes the valence of the metal ion, and stabilizes the structure of the metal halide salt. The residue of the organic halide generated by abstracting the halogen atom becomes an organic radical. A monomer is added to this organic radical, and polymerization proceeds. However, since the generated organic radical is unstable, it abstracts a halogen atom as a radical from the catalyst that has become a metal halide salt, and bonds to the original organic halide, which is stabilized. This prevents termination reactions such as coupling of the organic radical. The valence of the metal ion catalyst returns to the original value after the halogen atom is removed. In other words, the ATRP method is a polymerization method that utilizes an oxidation-reduction reaction, and the monomers are polymerized with organic halides as initiator groups by repeating the oxidation-reduction reaction, and a polymer grows. Since the radical concentration is low in this polymerization reaction, the monomers are added one to several molecules at a time, and grow, producing a polymer with a relatively uniform molecular weight. By applying this ATRP method to surface-initiated living radical polymerization, it is possible to form a dense polymer brush.

[0037] As the living radical polymerization method, the above-mentioned ATRP method using a conventionally known metal complex is suitable. As the metal complex, a metal complex having an element of Groups 7 to 11 of the periodic table as a central metal can be used. Specifically, metal complexes containing monovalent copper, divalent copper, divalent ruthenium, divalent iron, and divalent nickel can be mentioned. Among them, metal complexes containing monovalent copper and divalent copper, which are inexpensive and easily available, are preferred, and cuprous chloride, cupric chloride, cuprous bromide, cupric bromide, cuprous iodide, and cupric iodide are more preferred.

[0038] When a copper metal complex is used as a polymerization catalyst, a polyamine is used as a ligand for forming the complex. Examples of polyamines used as ligands include 2,2-bipyridine, dinonyl bipyridine, phenanthroline, tridimethylaminoethylamine, pentamethyldiethylenetriamine, tris[2-(dimethylamino)ethyl]amine, tris(2-picolyl)amine, and N,N,N',N'-tetrakis(2-pyridylmethyl)ethylenediamine. The amount of the metal complex (polymerization catalyst) relative to the methacrylate monomer is preferably 0.001 to 0.1% by mass.

[0039] In order to prevent the deactivation of the catalyst during polymerization, a reducing agent may be used. Examples of the reducing agent include tin dilaurate and ascorbic acid. In addition, an azo-based polymerization initiator such as azobisisobutyronitrile may be added to promote the activation of the polymerization. The ATRP method may be bulk polymerization or solution polymerization using an organic solvent or the like.

[0040] It is also preferable to polymerize a methacrylate monomer in the presence of a general-purpose organic compound that does not use heavy metals. As a method for polymerizing in the presence of an organic compound, a reversible catalyst-mediated polymerization method (RCMP method) can be mentioned. Specifically, it is preferable to polymerize by immersing a substrate in a polymerization system containing at least one salt selected from the group consisting of quaternary ammonium halide salts, quaternary phosphonium halide salts, and alkali metal halide salts. This allows polymerization using commercially available inexpensive organic materials and inorganic salts. In addition, since there is no need to remove metals, the burden on the environment can be reduced and the process can be simplified.

[0041] Examples of the quaternary ammonium halide salt include benzyltrimethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium iodide, tetraoctylammonium iodide, nonylpyridinium chloride, and choline chloride. Examples of the quaternary phosphonium halide salt include tetraphenylphosphonium chloride, methyltributylphosphonium bromide, and tetrabutylphosphonium iodide. Examples of the alkali metal halide salt include lithium bromide, potassium iodide, and sodium iodide.

[0042] As the salt, it is preferable to use an iodide salt. By using an iodide salt, living radical polymerization proceeds, and a precursor polymer with a narrower molecular weight distribution can be formed. In addition, it is preferable to use a salt that can be dissolved in a polymerization solution, such as a quaternary ammonium iodide salt, a quaternary phosphonium iodide salt, and an alkali metal iodide salt, and it is more preferable to use a quaternary ammonium iodide salt. Examples of the quaternary ammonium iodide salt include benzyltetrabutylammonium iodide, tetrabutylammonium iodide, tetraoctylammonium iodide, dedosyltrimethylammonium iodide, octadecyltrimethylammonium iodide, and trioctadecylmethylammonium iodide. These salts are used as catalysts and are different from the organic salts described above. In addition, since these salts are used as catalysts, the amount of addition is extremely small compared to the organic salts described above.

[0043] From the viewpoint of increasing the activity and forming a more concentrated and high molecular weight polymer (i), the amount of the salt relative to the polymerization initiating group is preferably at least an equimolar amount, more preferably at least 10 times the molar amount, and may be at least 100 times the molar amount.

[0044] The polymerization reaction is usually carried out under normal pressure conditions. However, in order to stably form a high molecular weight polymer (i), it is preferable to extend the polymerization time while suppressing the termination reaction derived from the radical polymerization. For this reason, it is preferable to polymerize the methacrylate monomer under a pressure (external pressure) condition of preferably 10 to 200 MPa, more preferably 20 to 100 MPa to form the polymer (i).

[0045] As the polymerization vessel, it is preferable to use a vessel that can be sealed and can withstand high pressure. In addition, since pressure needs to be transmitted to the inside of the vessel, it is preferable to use a vessel having a part that deforms under pressure, such as a soft part or an expandable part made of plastic. Specifically, various vessels such as polyethylene bottles, PET bottles, retort pouches, and blister containers can be used. In addition, a vessel made of a material that is not easily deformed at the temperature during polymerization and has heat resistance is preferable. Furthermore, a vessel made of a material that is not easily damaged by the solvent for polymerization and has properties such as chemical resistance and solvent resistance is preferable. Examples of materials that constitute the polymerization vessel include polyolefin resins, fluorine resins, polyester resins, polyamide resins, and engineering plastics. In addition, it is preferable to prevent gas from entering the polymerization vessel as much as possible during polymerization. For example, it is preferable to charge the polymerization solution to 90% or more of the volume of the polymerization vessel.

[0046] The number average molecular weight (Mn) of the polymer (i) is 500,000 to 5 million, preferably 800,000 to 4 million, more preferably 1 million to 3 million. If the Mn of the polymer (i) is less than 500,000, the thickness of the surface treatment film is insufficient. On the other hand, it is difficult to polymerize the polymer (i) having an Mn of more than 5 million, and the molecular weight distribution (PDI) may become excessively large due to the large number of termination reactions in side reactions. In this specification, the Mn and Mw of the polymer (i) are values ​​calculated as polymethyl methacrylate measured by gel permeation chromatography (GC).

[0047] The molecular weight distribution of the polymer (i) (PDI=weight average molecular weight (Mw) / number average molecular weight (Mn)) is 1.1 to 2.0, preferably 1.15 to 1.8, and more preferably 1.2 to 1.5. It is practically difficult to form a polymer (i) having a PDI of less than 1.1. On the other hand, if the PDI exceeds 2.0, the performance of the concentrated polymer brush may not be fully exhibited, and the smoothness of the surface treatment film may be somewhat reduced. By forming a polymer (i) having a relatively narrow molecular weight distribution, the growing ends of the polymer (i) are relatively uniform, and a surface treatment film having a relatively flat surface can be provided. In addition, by setting the Mn and PDI of the polymer (i) within the above ranges, the generation density of the polymer (i) relative to the substrate is high, and a surface treatment film that is a concentrated polymer brush of sufficient thickness can be obtained.

[0048] The Mn and Mw of the polymer (i) can be measured by removing the polymer (i) from the substrate. Methods for removing the polymer (i) from the substrate include a method of treating with hydrofluoric acid or concentrated alkali, a method of hydrolysis, and the like. In addition, a methacrylate monomer is polymerized in the presence of a compound having a polymerization initiator group (a so-called free initiator compound) to form a free polymer that is not bonded to the surface of the substrate. The Mn and Mw of the polymer stretched from the free initiator compound can be estimated as the Mn and Mw of the polymer (i).

[0049] The thickness of the surface treatment film provided on the substrate surface is 400 to 3,000 nm, preferably 500 to 2,000 nm, and more preferably 700 to 1,500 nm. If the thickness of the surface treatment film is less than 400 nm, it is difficult to exhibit the performance of the surface treatment film for modifying the surface of the substrate, and durability such as abrasion resistance is insufficient. On the other hand, in order to form a surface treatment film with a thickness of more than 3,000 nm, it is necessary to make the molecular weight of the polymer (i) very large, so that the polymerization time becomes excessively long and the molecular weight distribution of the polymer (i) may become too broad.

[0050] The amount of polymer (i) bound to the surface of the substrate is2 The molecular chain is 0.1 or more, preferably 0.2 or more, more preferably 0.1 to 1, and particularly preferably 0.15 to 0.7. 2 The amount of polymer (i) bonded per unit is the graft density σ (particles / nm 2 ) The polymer (i) is stretched from the polymerization initiation group on the surface of the substrate as the initiation point in a direction perpendicular to the substrate to form a surface treatment film. By setting the graft density σ of the polymer (i) within the above range, it is possible to exhibit properties such as high elasticity, ultra-low friction, and size exclusion effect. When the graft density σ is 0.1 strands / nm 2 If the number is less than 1, the above characteristics are not fully exhibited. 2 It is generally difficult to achieve a graft density σ greater than 100 nm.

[0051] Graft density σ (particles / nm 2 ) can be calculated by the following formula (A). The thickness of the surface treatment film can be measured by a conventionally known method using, for example, an ellipsometer, an electron microscope, an atomic force microscope, or the like. The density of the polymer (i) can be a value described in a conventionally known document or a value measured by a method described in JIS K 7112:1999, or the like. σ = dLNAMn (A) d: density of polymer (polymer (i)) L: Thickness of the polymer layer (surface treatment film) NA: Avogadro's number Mn: number average molecular weight of polymer (polymer (i))

[0052] The substrate (surface-modified substrate) on whose surface the surface treatment film formed by the above-mentioned manufacturing method is provided has a sufficient thickness, and the polymer (i) constituting the surface treatment film has a high molecular weight and is densely generated, so that the surface durability is high. In addition, by appropriately designing the type of polymer (i), a surface treatment film tailored to the application can be obtained. Since the substrate having the above-mentioned surface treatment film has excellent durability, it is also suitable for use under harsh conditions such as outdoor applications and sliding applications. Furthermore, by appropriately designing the monomer type, it is expected to exhibit performance such as low friction, anti-fogging properties, water repellency, oil repellency, contamination resistance, size exclusion properties, protein adhesion prevention, antibacterial properties, and high virus resistance. The substrate provided with the surface treatment film manufactured by the above-mentioned manufacturing method is suitable as an article used in various fields such as medical materials, electronic materials, display materials, semiconductor materials, machine parts, sliding members, and battery materials. EXAMPLES

[0053] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified.

[0054] <Production of surface-modified substrate> Example 1 A silicon substrate measuring 1 cm x 1 cm was prepared. The surface of the silicon substrate was ultrasonically cleaned with isopropyl alcohol (IPA), and then irradiated with UV ozone using a tip cleaner (manufactured by Bioforce Nanoscience Co., Ltd.) to form hydroxyl groups on the surface of the silicon substrate, activating it. The activated silicon substrate was immersed for 12 hours in a container containing 100 parts of ethanol, 10 parts of 28% aqueous ammonia solution, and 1 part of 2-bromo-2-methylpropionyloxypropyltrimethoxysilane (BPM). The removed silicon substrate was dried at 80°C for 10 minutes to obtain a silicon substrate (substrate) having a polymerization initiation group on its surface.

[0055] In a glass sample bottle, 0.0170 parts of copper bromide (CuBr), 0.0013 parts of copper bromide (CuBr2), 0.1485 parts of dinonyl bipyridine (dNbyp), 8.8331 parts of methyl methacrylate (MMA), 8.5 parts of tetraethylammonium p-toluenesulfonate (TEA-PTS, solid at 25 ° C.), 6.4 parts of propylene glycol (PG), and 1.0 parts of a 0.00958% methyl methacrylate solution of ethyl bromoisobutyrate (EBIB) (EBIB solution) were put and homogenized to obtain a brownish-brown polymerization solution. The concentration of TEA-PTS in the polymerization solution was 56.9%.

[0056] 10 parts of the polymerization solution and the substrate were placed in a container. After argon gas was blown in for 30 minutes, the lid was closed and the container was placed in a high-pressure device (trade name "PV-400", manufactured by Shin Corporation) containing water as a pressure medium, and polymerization was carried out for 4 hours under conditions of 60°C and 100 MPa to form polymer (i). After cooling, a part of the polymerization solution in the container was sampled, and the number average molecular weight (Mn) of the formed polymer (i) in terms of polymethyl methacrylate (PMMA) was measured by gel permeation chromatography (GPC) using dimethylformamide (DMF) as a developing solvent, and the molecular weight distribution (PDI = Mw / Mn) was calculated. The Mn of the formed polymer (i) was 2.03 million, and the PDI was 1.83.

[0057] The contents removed from the container were immersed in tetrahydrofuran (THF) for 12 hours and then dried to obtain a surface-modified substrate in which a surface treatment film exhibiting rainbow interference was provided on the surface of the silicon substrate. The thickness of the surface treatment film measured using a film thickness meter (product name "F20-UV", Filmetrics, Inc.) was 878 nm. The graft density σ calculated from the Mn of polymer (i), the thickness of the surface treatment film, and the density of PMMA (1.2) was 0.31 strands / nm 2 It was.

[0058] (Examples 2 to 9) A surface-modified substrate having a surface treatment film provided on the surface of a silicon substrate was obtained in the same manner as in Example 1, except that the composition of the polymerization solution and the polymerization conditions were as shown in Table 1. The meanings of the abbreviations in Table 1 are as follows. DMP-PTS: 1,4-dimethylpyridinium p-toluenesulfonate (solid at 25°C) TEA-MS: Tetraethylammonium methylsulfonate (solid at 25°C) Betaine: Trimethylglycine (solid at 25°C) DMF: Dimethylformamide

[0059] TIFF0007656298000007.tif130170

[0060] Example 10 A silicon substrate (substrate) identical to the silicon substrate having a polymerization initiation group on its surface used in Example 1 was prepared. 0.0170 parts of CuBr, 0.0013 parts of CuBr, 0.1485 parts of dNbpy, 8.8331 parts of polyethylene glycol monomethyl ether methacrylate (PEGMA), 8.5 parts of TEA-PTS, 6.5 parts of PG, and 1.0 parts of EBIB solution were put into a glass sample bottle and homogenized to obtain a brownish-red polymerization solution. The concentration of TEA-PTS in the polymerization solution was 56.9%. Using the obtained polymerization solution and the prepared substrate, the polymerization was carried out for 4 hours under conditions of 60°C and 100 MPa, as in Example 1 described above, to form a polymer (i), and a surface-modified substrate in which a surface treatment film was provided on the surface of the silicon substrate was obtained. The Mn of the formed polymer (i) was 2.2 million, and the PDI was 1.83. The thickness of the surface treatment film was 823 nm, and the graft density σ calculated from the Mn of polymer (i), the thickness of the surface treatment film, and the density of polyPEGMA (1.15) was 0.26 / nm 2 It was.

[0061] Example 11 Except for using 8.8331 parts of dimethylaminoethyl methacrylate (DMAEMA) instead of PEGMA and DMF instead of PG, polymer (i) was formed in the same manner as in Example 10 described above, and a surface-modified substrate in which a surface treatment film was provided on the surface of a silicon substrate was obtained. The Mn of polymer (i) was 2.3 million, and the PDI was 1.75. The thickness of the surface treatment film was 854 nm, and the graft density σ calculated from the Mn of polymer (i), the thickness of the surface treatment film, and the density of polyDMAEMA (1.15) was 0.25 strands / nm 2 It was.

[0062] (Reference example 1) Except for using anisole instead of PG and changing the pressure during polymerization to 400 MPa, polymer (i) was formed in the same manner as in Example 1 described above, and a surface-modified substrate was obtained in which a surface treatment film was provided on the surface of a silicon substrate. The Mn of polymer (i) was 1.77 million, and the PDI was 1.23. The thickness of the surface treatment film was 901 nm, and the graft density σ was 0.36 fibers / nm 2 It was.

[0063] This reference example is an example in which polymerization was performed under ultra-high pressure conditions of 400 MPa to prevent termination reaction and accelerate the growth reaction of polymer (i). In Example 1, polymerization was performed under medium pressure conditions of 100 MPa, and polymer (i) with the same molecular weight and graft density as Reference Example 1, polymerization was performed under ultra-high pressure conditions of 400 MPa, and a surface treatment film with the same thickness was formed. The apparatus for polymerization under ultra-high pressure conditions of 400 MPa is a special apparatus made of heavy steel that can withstand ultra-high pressure, and is often a custom-made product. In contrast, the apparatus for polymerization under medium pressure conditions of 100 MPa is a commercially available apparatus that is also used in food manufacturing and the like and is easily available. Therefore, the method for producing a surface treatment film of the present invention is a method that can be easily implemented using commercially available equipment that is easily available, and is suitable for commercialization.

[0064] (Reference example 2) Except for using methylimidazolium bis(trifluoromethyl)sulfonimide salt, an ionic liquid, instead of PG, polymer (i) was formed in the same manner as in Example 1 described above, and a surface-modified substrate was obtained in which a surface treatment film was provided on the surface of a silicon substrate. The Mn of polymer (i) was 1.25 million, and the PDI was 1.29. The thickness of the surface treatment film was 738 nm, and the graft density σ was 0.41 fibers / nm 2 It was.

[0065] This reference example is an example in which a highly polar ionic liquid is used as a solvent during polymerization to accelerate the growth reaction of polymer (i). Even in Example 1, in which polymerization was performed using a general solvent (PG) other than an ionic liquid, a polymer (i) having a molecular weight and graft density equivalent to those in Reference Example 2 was formed, and a surface treatment film of equivalent thickness was formed. Ionic liquids are not particularly inexpensive. In contrast, the method for producing a surface treatment film of the present invention, which uses a highly versatile organic solvent such as PG and an organic salt, contributes to reducing the production cost of the surface treatment film and is suitable for commercialization.

[0066] Comparative Example 1 Except for not using the organic salt (TEA-PTS), the polymer (i) was formed in the same manner as in Example 1 described above, and a surface-modified substrate was obtained in which a surface treatment film was provided on the surface of a silicon substrate. The Mn of the polymer (i) was 320,000, and the PDI was 3.83. The thickness of the surface treatment film was 78 nm, and the graft density σ was 0.17 strands / nm 2 It was.

[0067] Comparative Example 2 Except for not using the organic salt (TEA-PTS), the polymer (i) was formed in the same manner as in Example 4 described above, and a surface-modified substrate was obtained in which a surface treatment film was provided on the surface of a silicon substrate. The Mn of the polymer (i) was 270,000, and the PDI was 1.23. The thickness of the surface treatment film was 110 nm, and the graft density σ was 0.29 strands / nm 2 It was.

[0068] Comparative Example 3 Except for using tetraethylammonium chloride instead of TEA-PTS, an attempt was made to form polymer (i) in the same manner as in Example 1 described above, but polymer (i) could not be formed and a surface-modified substrate could not be obtained. It is believed that the chloride ions of tetraethylammonium chloride inhibited atom transfer radical polymerization. [Industrial Applicability]

[0069] The surface treatment film produced by the production method of the present invention is a concentrated polymer brush, and can impart properties such as high resilience, hydrophilicity, and water repellency to the surface of a substrate. Furthermore, by swelling, it can exhibit properties such as extremely low friction, size exclusion properties, contamination resistance, and high adhesion prevention properties, making it useful as a material applied to parts of automobiles, aircraft, electronic devices, home appliances, battery components, medical materials, display materials, etc. In addition, according to the production method of the present invention, the concentrated polymer brush can be easily produced using inexpensive equipment and inexpensive materials, making it suitable for mass production.

Claims

1. The method includes a step of performing surface radical polymerization of a methacrylate monomer in the presence of a substrate having a functional group represented by the following general formula (1) on its surface and a polymerization solution, to form a surface treatment film containing a polymer (i) having one end bonded to the surface of the substrate, The polymer (i) has a number average molecular weight of 500,000 to 5,000,000 and a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.1 to 2.0; The thickness of the surface treatment film is 400 to 3,000 nm, The amount of the polymer (i) bound to the surface of the substrate is within 1 nm 2 0.1 molecular chain or more per unit area, the polymerization solution is a solution in which ethyl bromoisobutyrate and an organic salt that is solid at 25° C. are dissolved in an organic solvent, and the concentration of the organic salt is 10 to 90 mass %, The method for producing a surface treatment film, wherein the organic salt is a quaternary ammonium salt whose counter ion is a non-halogen anion. (In the above general formula (1), A represents O or NH, and R 1 represents a hydrogen atom, an alkyl group, an acyl group, or an aryl group; R 2 represents an alkyl group or an aryl group, X represents a chlorine atom, a bromine atom, or an iodine atom, and "*" represents the bonding position with the surface of the substrate.

2. The method for producing a surface treatment film according to claim 1 , wherein the organic salt is represented by the following general formula (2) or (3): (In the above general formula (2), R 3 , R 4 , R 5 , and R 6 are each independently an alkyl group having 1 to 18 carbon atoms or a benzyl group, and A is a non-halogen anion. (In the general formula (3), R 7 represents a hydrogen atom or an alkyl group having 1 to 18 carbon atoms; R 8 represents an alkyl group having 1 to 18 carbon atoms, and A represents a non-halogen anion.

3. 3. The method for producing a surface treatment film according to claim 1, wherein the non-halogen anion is at least one selected from the group consisting of a methanesulfonate ion, an ethanesulfonate ion, a benzenesulfonate ion, and a toluenesulfonate ion.

4. The method for producing a surface treatment film according to any one of claims 1 to 3, wherein the organic solvent is at least one selected from the group consisting of alkylene (carbon number 2 to 4) glycol, poly(n = 2 to 3) alkylene (carbon number 2 to 4) glycol, alkylene (carbon number 2 to 4) glycol monoalkyl (carbon number 1 to 4) ether, and poly(n = 2 to 3) alkylene (carbon number 2 to 4) glycol monoalkyl (carbon number 1 to 4) ether.

5. The method for producing a surface treatment film according to any one of claims 1 to 4, wherein the functional group represented by the general formula (1) is at least one of a 2-bromo-2-methylpropanoyloxy group and a 2-bromo-2-methylpropanoylamino group.

6. The method for producing a surface-treated film according to any one of claims 1 to 5, wherein the methacrylate monomer is subjected to surface-initiated living radical polymerization under a pressure condition of 10 to 200 MPa.

Citation Information

Patent Citations

  • Solid with grafted surface and its production

    JP1999263819A

  • Slide mechanism and slide member

    JP2014169787A

  • High molecular weight zwitter ion-containing polymer

    JP2016040371A

  • Method for producing polymer

    JP2018162333A

  • Production method and inspection method of surface-modified substrate

    JP2020045428A